The unexpected in Juan Ramón Jiménez - Laia Olivé (Études romanes de Brno, 2024)
Although Juan Ramón Jiménez is well-known especially due to his lyrical poetry, he is the author of numerous prose texts, among which many of them are narrative. Both forms frequently include unusual elements related to what the poet calls "the invisible reality", which seeps into the "visible reality" producing a strangeness in the ones who perceive these events. These occurrences set Jiménez's work closer to the literature of the unexpected and its different manifestations: the fantastic, the strange and what we name the mysterious, which is present in poetry. Departing from a theoretical exposition, this article shows how the unexpected appears in some texts by Juan Ramón.